Optimalisasi Katekese Sekolah: Mengintegrasikan Strategi Pedagogis dan Pembentukan Iman untuk Perkembangan Siswa Secara Holistik - Anggal, Nikolaus (PT Literasi Nusantara Publisher, 2024)
This article explores the pivotal role of religious education, particularly school catechesis, in molding the character and comprehensive development of students. While catechesis is acknowledged as the primary vehicle for imparting religious teachings, the persistent challenge lies in seamlessly integrating pedagogical strategies with faith formation. Employing a literature review method, the research identifies previously proposed and implemented pedagogical strategies and concepts of faith formation. The findings underscore the significance of catechesis within a flexible curriculum, effective pedagogical approaches (interactive, technological, critical skills), and the catechesis method in faith education. The conclusion underscores the vital role of school catechesis in shaping an independent, creative, and faith-centric younger generation with spiritual values. Recognized issues encompass the efficacy of teaching methods, integration of religious learning with broader student development, and hurdles in student motivation. Cultural shifts and technological progress also impact catechesis effectiveness in schools. In the context of a flexible curriculum, school catechesis is expected to leverage its adaptability to foster a more dynamic and inclusive learning environment. Teachers can integrate interactive learning methods and technology, concentrating on cultivating students' critical and analytical skills. The significance of the catechesis approach is also highlighted in guiding students through moral and spiritual challenges in a complex society. School catechesis additionally contributes to nurturing tolerance, appreciation for religious diversity, and the formation of personalities grounded in Catholic faith teachings.